The Phenomenon of “Literally” Slang Term on Twitter: Semantics View - Berita Mambarasi Nehe; putriana Salsabila (English Education, Linguistics, and Literature Journal, 2023)
This study focused on using “literally” slang terms on Twitter which aims to find out what the meaning of language variations. This research uses a qualitative approach, with a descriptive analysis method. The way to collect the data is the statements taken from Twitter as media used by people. this study showed that the use of literally word that happened nowadays had many purposes and meaning conveyed by the person. The finding of the research are the people use literally term to emphasize, surprised and the meaning is real not figurative on what she/he stated on their Twitter account. The conclusion is the use of slang must be in accordance with the context when, where, with whom to speak because not all slang terms are used in all situations. The use of slang can be used among teenagers, among colleagues, in casual or informal situations. Users of slang terms must be smart in placing the words because if they do not know how to place the words, they will be considered as an impolite or arrogant person by others. From the results of the research above, tweet users use the word literally by giving the meaning is not out of the context of speech, the meaning is acceptable and understandable by others